\[\ \overline{z_{1} + z_{2}} = \overline{z_{1}} + \overline{z_{2}}.\]
\[\overline{z_{1} + z_{2}} =\]
\[= \overline{\left( x_{1} + iy_{1} \right) + \left( x_{2} + iy_{2} \right)} =\]
\[= \overline{\left( x_{1} + x_{2} \right) + \left( y_{1} + y_{2} \right)i} =\]
\[= \left( x_{1} + x_{2} \right) - \left( y_{1} + y_{2} \right)i;\]
\[\overline{z_{1}} + \overline{z_{2}} = \overline{x_{1} + iy_{1}} + \overline{x_{2} + iy_{2}} =\]
\[= \left( x_{1} - iy_{1} \right) + \left( x_{2} - iy_{2} \right) =\]
\[= \left( x_{1} + x_{2} \right) - \left( y_{1} + y_{2} \right)i.\]
\[Что\ и\ требовалось\ доказать.\]